An innovative approach to educating nurses to clinical competence: A randomized controlled trial. (November 2018) - Lengetti, Evelyn; Kronk, Rebecca; Ulmer, Karen W.; Wilf, Karen; Murphy, Diane; Rosanelli, Margaret; Taylor, April
Abstract: Aim: This study examined the effect of mastery learning on new graduate nurses' skill and self-regulation practices for indwelling urinary catheter insertion in a simulated learning environment. Background: Clinical competence is a patient safety imperative, it is therefore important to use the most effective approaches to prepare competent nurses resulting in improved patient care and clinical outcomes. Catheter associated Urinary Tract Infections (CaUTI) are a nursing quality indicator, and account for 30% of all Hospital-Acquired Conditions (HAC) annually in the US. Design: A longitudinal randomized control trial to compare two learning groups. Setting: Large acute care health system. Participants: 40 Nurses with a Bachelor of Science Degree in Nursing (BSN) and who were new graduate nurses. Method: Participants were randomized into the experimental group (mastery learning) or the control group (traditional learning). Both groups were asked to complete a self-paced computerized instructional module that reviewed the procedural steps for the insertion of an indwelling urinary catheter in a female prior to the initial assessment. This study examined performance of insertion of a urinary catheter initially and at one-month post intervention and the self-regulation practices of all participants. Results: The mean Survey of Academic Self-Regulation (SASR) scores between groups was significant, p = .035. The mean change in the Performance Assessment Tool (PAT) 17-critical steps scores between groups was also significant, p = .013. Conclusion: Retention of the critical steps is valuable because if performed incorrectly, these steps may cause harm to the patient. Self-regulation practices promote confidence and an intrinsic motivation to ask for help when clinical practice questions arise.